Sistem Pakar Dan Layanan Konsultasi Kesehatan Mental Remaja Menggunakan Metode Forward Chaining Berbasis Website - Arif -; Tomi Tristono; Candra Budi Susila (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2024)
Mental health has become an increasingly important issue in today's society. However, awareness of the importance of mental health, especially among teenagers, is still lacking. Mental health services are generally conducted in person, which causes many people to be hesitant or have difficulty accessing them. Additionally, detecting someone's mental health requires the assistance of a psychologist. To address these issues, an expert system and counseling service for adolescent mental health are developed using the forward chaining method based on a website platform. This system is developed using the waterfall method and programmed in the PHP (native PHP) programming language. The system's testing is conducted using black box testing. With the existence of this expert system, it is hoped that awareness and understanding of mental health will increase, aiding in the detection of individuals' mental health and providing easy access for them to receive the necessary assistance. The results of the system's testing using black box testing for the developed system show a success rate of 100%.